Development of Chemistry Learning Achievement in Stoichiometry by an Active Learning Lesson Using Team-Based Learning for High School Students - Boonnom, Suwisa; Dornbundit, Piyarat (Science Essence Journal, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีจุดประสงค์เพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนวิชาเคมี เรื่อง ปริมาณสารสัมพันธ์ ของนักเรียนระดับมัธยมศึกษาตอนปลายก่อนและหลังการเรียนรู้โดยใช้บทเรียนเชิงรุกร่วมกับการจัดการเรียนรู้แบบใช้ทีมเป็นฐาน และเพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนวิชาเคมี เรื่อง ปริมาณสารสัมพันธ์ ของนักเรียนระดับมัธยมศึกษาตอนปลายกลุ่มทดลอง หลังการเรียนรู้โดยใช้บทเรียนเชิงรุกร่วมกับการจัดการเรียนรู้แบบใช้ทีมเป็นฐาน เทียบกับกลุ่มควบคุม กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้เป็นนักเรียนชั้นมัธยมศึกษาปีที่ 5 โรงเรียนระดับมัธยมศึกษาขนาดใหญ่พิเศษแห่งหนึ่ง ภาคเรียนที่ 1 ปีการศึกษา 2561 จำนวน 2 ห้องเรียนซึ่งได้มาโดยใช้วิธีการเลือกแบบเฉพาะเจาะจง (purposive sampling) แบ่งออกเป็นกลุ่มทดลอง 1 ห้องเรียน จัดการเรียนรู้เรื่อง ปริมาณสารสัมพันธ์ โดยใช้บทเรียนเชิงรุกร่วมกับการจัดการเรียนรู้แบบใช้ทีมเป็นฐาน และกลุ่มควบคุม 1 ห้องเรียน จัดการเรียนรู้แบบปกติ เครื่องมือที่ใช้ในการวิจัยครั้งนี้ คือ (1) บทเรียนเชิงรุกร่วมกับการจัดการเรียนรู้แบบใช้ทีมเป็นฐาน (2) แบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน เรื่อง ปริมาณสารสัมพันธ์ เป็นแบบปรนัย 4 ตัวเลือก จำนวน 25 ข้อ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน ทดสอบสมมติฐานโดยใช้ t-test for dependent samples และ t-test for independent samples ผลการวิจัยปรากฏดังนี้ (1) นักเรียนกลุ่มทดลองมีผลสัมฤทธิ์ทางการเรียนเพิ่มสูงขึ้นจากก่อนเรียน อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 (2) นักเรียนกลุ่มทดลองมีผลสัมฤทธิ์ทางการเรียนวิชาเคมีเรื่อง ปริมาณสารสัมพันธ์ สูงกว่ากลุ่มควบคุม อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 คำสำคัญ: ผลสัมฤทธิ์ทางการเรียน ปริมาณสารสัมพันธ์ การเรียนรู้เชิงรุก ทฤษฎีการสร้างองค์ความรู้ด้วยการมีปฏิสัมพันธ์ทางสังคม รูปแบบการเรียนรู้แบบใช้ทีมเป็นฐาน ABSTRACT The purposes of this research were to compare the chemistry learning achievement in stoichiometry of high school students before and after using an active learning lesson with Team-Based Learning and compare the chemistry learning achievement in stoichiometry in the experimental and control groups. The samples in this research were two classrooms by purposive sampling from the first semester of the academic year of 2018 eleventh grade students in an extra large school in Bangkok. One of the collected classrooms was assigned to be the experimental group and studied by the active learning lesson using Team-Based Learning. Another classroom was assigned to be the control group and studied by the traditional learning approach. The research instruments consisted of the following: (1) the active learning lesson using Team-Based Learning (2) the twenty-five items of four multiple choices achievement test. The statistics used to analyze the collected data were the mean and standard deviation. The statistics used for hypothesis test were t-test for dependent samples and t-test for independent samples. The results of the study showed that the experimental group achieved higher average posttest score than pretest at .01 level of significance and higher average posttest score than the control group at .01 level of significance. Keywords: learning achievement, stoichiometry, active learning, social constructivist theory, team-based learning